Genetic Polymorphisms Study of Polycystic Ovary Syndrome Associated with Omentin-1V109D Gene in Iraqi WomenGenetic Polymorphisms Study of Polycystic Ovary Syndrome Associated with Omentin-1V109D Gene in Iraqi Women - Lujaen A. Hameed; Shiva Khezri; Ilham A. Khalaf; Zainab J. Ghaneim; Alaa A. Al-Asadi (Iraqi Journal of Industrial Research)
Polycystic ovary syndrome (PCOS) is the most frequent endocrinological disorder, occurring in young women at reproductive age. This study was carried out to investigate the association between the fat mass and obesity associated gene (Omentin-1V109D gene) polymorphism with some physiological and biochemical Parameters. The present study indicates to the association between PCOS patients and control groups according to the hormonal profile and there is a link between obesity and pathogenesis of hyperprolactinemia, our data showed highly significantly difference. This study shows demonstrated the comparison of the mean of selected Lipid profile between PCOS patients and control group involving (T. Cholesterol, Triglyceride, HDL, LDL and VLDL). The mean value of serum total cholesterol (T.C), Triglyceride, HDL, LDL and VLDL are highly significantly increased (p<0.01) in PCOS patients group compared with healthy group (control). It was found highly significant association (P≤0.01) of serum-FSH, serum-LH, testosterone and prolactin hormones. It was found the mean value of serum total cholesterol, triglyceride, HDL, LDL and VLDL are highly significantly (P≤0.01) increased in PCOS patients. The Omentin gene (V109D rs2274907A) polymorphism have a significant association with hyper LDL, in women with PCO, and may represent as a risk factor for PCOS incidence.